SCIENTIFIC AND THEORETICAL INTERPRETATION OF SOCIO-PSYCHOLOGICAL ASPECTS OF SANOGENIC THINKING - Abdurahmоnova Zuhra (Galaxy International Interdisciplinary Research Journal, 2021)
The article presents a socio-psychological classification of sanogenic thinking. The advanced experience of foreign scientists makes it possible to analyze the traditions of the scientific and theoretical study of the socio-psychological aspects of Sanogen thinking.